2022
DOI: 10.1017/s0033291722000563
|View full text |Cite
|
Sign up to set email alerts
|

Coping with COVID: risk and resilience factors for mental health in a German representative panel study

Abstract: Background: The COVID-19 pandemic might affect mental health. Data from population-representative panel surveys with multiple waves including pre-COVID data investigating risk and protective factors are still rare. Methods: In a stratified random sample of the German household population (n=6,684), we conducted survey-weighted multiple linear regressions to determine the association of various psychological risk and protective factors assessed between 2015 and 2020 with changes in psychological distress (PD; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 79 publications
3
22
1
Order By: Relevance
“…The few representative studies analyzing individual mental health trajectories identify most people as resilient, while 7% to 11% of individuals reported mental health decline ( 9 , 10 , 16 ) vs. 9–12% experiencing improvements ( 10 , 16 ). This pattern in mental health development over time has also been found in population-based surveys conducted in Germany ( 17 , 18 ): Based on the same instrument as used in the present study to assess anxiety and depression, an initial increase in anxiety and depression was found in early stages of the pandemic, which was again reduced during the second wave of the pandemic ( 18 ), but overall higher scores of anxiety and depression were reported peri-pandemic as compared to pre-pandemic years ( 17 ). Consistently, a recent meta-analysis on lockdown effects on population mental health concludes that most individuals stay mentally healthy ( 8 ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The few representative studies analyzing individual mental health trajectories identify most people as resilient, while 7% to 11% of individuals reported mental health decline ( 9 , 10 , 16 ) vs. 9–12% experiencing improvements ( 10 , 16 ). This pattern in mental health development over time has also been found in population-based surveys conducted in Germany ( 17 , 18 ): Based on the same instrument as used in the present study to assess anxiety and depression, an initial increase in anxiety and depression was found in early stages of the pandemic, which was again reduced during the second wave of the pandemic ( 18 ), but overall higher scores of anxiety and depression were reported peri-pandemic as compared to pre-pandemic years ( 17 ). Consistently, a recent meta-analysis on lockdown effects on population mental health concludes that most individuals stay mentally healthy ( 8 ).…”
Section: Introductionsupporting
confidence: 75%
“…Taking a longer-term perspective, it will be an important question if elevated mental health burden throughout the pandemic puts individuals at risk to develop clinical mental health conditions, and, on a population-level, if and when overall mental health status recovers to pre-pandemic levels. A further pivotal line of research focuses on predictors of both, mental health deterioration and mental resilience throughout the pandemic on a population level and in vulnerable subgroups ( 17 , 31 ). Knowledge on such risk and protective factors will inform tailored prevention efforts and intervention strategies for future pandemic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This vulnerability to stressful events in depression may become particularly relevant in times in which individuals are faced with an inevitable stressor such as the COVID-19 pandemic that may threaten mental health. This assumption is corroborated by reports of increases in experienced distress, anxiety, depression, and loneliness from the time before the pandemic to the first wave of the pandemic in Germany [12,13] and countries worldwide [14]. Recent studies on the longitudinal course of mental health during the COVID-19 pandemic revealed that anxiety, depression, and loneliness decreased during the easing of the first lockdown [15][16][17][18][19], but, again, increased while lockdown measures were extended and during the second and third COVID-19 waves in Europe [20,21].…”
Section: Introductionmentioning
confidence: 65%
“…Recent studies on the longitudinal course of mental health during the COVID-19 pandemic revealed that anxiety, depression, and loneliness decreased during the easing of the first lockdown [15][16][17][18][19], but, again, increased while lockdown measures were extended and during the second and third COVID-19 waves in Europe [20,21]. In contrast, there are studies demonstrating that mental health problems were relatively stable over time or even decreased during the COVID-19 pandemic [13,[22][23][24]. These inconsistent findings might be partly explained by differences in the composition of study populations and timing of the assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, two thirds of the reviewed studies are based on data collected during the first wave and the summer plateau of 2020, when COVID-19 incidence was comparatively low in Germany (35). The few studies that address the later course of the pandemic find an elevated frequency of depressive symptoms in the first months of 2021 (36,37) or of depressive and anxiety symptoms into later 2020 (37,38) compared to pre-pandemic data and an increase in mental distress (39) but a decrease in depressive and anxiety symptoms (37) in the second wave compared to the first wave. Further results from representative surveys spanning the whole pandemic period and allowing for comparisons to pre-pandemic baseline data are needed in order to adequately assess the mental health impact of the pandemic in the general population in Germany.…”
Section: Despite the Well-founded Expectation Of A Mental Health Cris...mentioning
confidence: 99%